GAMBARAN PERSEPSI MASYARAKAT TERHADAP PERAN DAN MOTIVASI BIDAN UNTUK MENURUNKAN ANGKA KESAKITAN DBD DI DESA SIAGA MORGO MULYO TAHUN 2017 - Rina, Rina (Journal Of Midwifery, 2018)
The high rate of morbidity and death from dengue fever is an infectious disease whose efforts to reduce the case related to national commitment and often appear as extraordinary events, this is seen from the high number of dengue cases in Indonesia as many as 8,487 people with Dengue Fever with the number of deaths 108 people and Bengkulu Province case encountered as many as 925 cases, and died 19 people, so the role of midwife as the spearhead in society is needed. This research aimed to find out the perception of society to the Role and Motivation of Midwife to Reduce the Figures of Dengue Fever in Siaga Morgo Mulyo village in 2017.This research is a descriptive research, the population were all families in Siaga Morgo Mulyo village in 2017 totaled 320 heads of family and the sample taken 39 people with purposive sampling sampling technique, with inclusion criterion sample which were those who were willing to become respondents and had an ability in read and writing.The results of this study indicated that people's perception on the role and motivation of midwives to reduce Dengue Fever morbidity in Siaga Morgo Mulyo village in 2017, most of the respondents (62.5%) had less perception on the role of midwives and almost all respondents (51.3 %) had less perception on midwife’s motivation to Reduce Dengue Fever Mortality Rate In Siaga Morgo Mulyo village in 2017.It is expected that medics especially midwives can emphasize by performing their role and motivation as midwife in reducing Dengue Fever morbidity.